PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP TINGKAT PENJUALAN JIG DI PT. MITRA GLOBAL BERSAMA - Doloksaribu, Sartika; Wibowo, Edwin Agung (BENING, 2017)
Â This study aims to determine the effect Product Quality And Price On The Level Sales in PT.Mitra Global Joint Jig in Batam. This research was conducted with pedekatan survey consists of variable Product Quality and Price (X), and the rate of Sales (Y). To prove the influence of Product Quality and Price on the level of sales, the authors collected data by distributing questionnaires as much as 39 respondents in the sample taken from customers Jig in PT.Mitra Global Shared ever used the product JIG. Data were collected through questionnaires were processed using the application program Statistical Product and Service Solutions (SPSS) version 20. The results showed that the variable quality of the product (X1) individually do not have a positive and significant impact on the level of sales variable (Y), it can seen in a positive regression coefficient (0.652 (2,042) and the numeric significance of 0.519 (greater than 0.05), while the price variable (X2) individually have a positive influence and signifiikan to variable rate of sales (Y), it is can be seen in a positive regression coefficient (3.750)) t table (2.042) and a significant number of 0.001 (less than 0.05). Product Quality and Price together contribute to providing a positive and significant effect on the level of sales by 30% while the remaining 70% are influenced by other factors. Partial regression analysis results indicate that the variable quality of individual products do not affect the level of sales, while the price variables individually have a positive and significant impact on the level of sales.